소형위성용 모터 구동형 포커싱 메커니즘 - 정진원(Jinwon Jung); 최준우(Junwoo Choi); 이동규(Dongkyu Lee); 황재혁(Jaehyuck Hwang); 김병규(Byungkyu Kim) (항공우주시스템공학회지, 2018)
The working principle of a satellite camera involves a focusing mechanism for controlling the focus of the optical system, which is essential for proper functioning. However, research on focusing mechanisms of satellite optical systems in Korea is in the beginning stage and developed technology is limited to a thermal control type. Therefore, in this paper, we propose a motor-driven focusing mechanism applicable to small satellite optical systems. The proposed mechanism is designed to generate z-axis displacement in the secondary mirror by a motor. In addition, three flexure hinges have been installed on the supporter for application of preload on the mechanism resulting in minimization of the alignment error arising due to manufacturing tolerance and assembly tolerance within the mechanism. After fabrication of the mechanism, the alignment errors (de-space, de-center, and tilt) were measured with LVDT sensors and laser displacement meters. Conclusively, the proposed focusing mechanism could achieve proper alignment degree, which can be applicable to small satellite optical system. 위성용 카메라의 경우 광학계의 초점을 제어하기 위한 포커싱 메커니즘이 필수적이다. 그러나 국내의 위성용 광학계 포커싱 메커니즘 관련 연구는 시작 단계이며, 관련 보유 기술 또한 열제어형에 국한되어있다. 따라서 본 논문에서는 소형위성용 광학계에 적용 가능한 모터 구동형 포커싱 메커니즘을 제안하였다. 제안된 메커니즘은 모터 구동에 의해 secondary mirror에 z축 변위를 발생시키도록 설계하였다. 또한 서포터에 flexure hinge를 설치하여 사전하중을 가하도록 하여 메커니즘내 부품간 제작공차 및 조립공차로 인한 정렬도 오차를 최소화하도록 하였다. 메커니즘 제작 후 LVDT 센서(linear variable differential transformer sensor)와 레이저 변위측정기로 정렬도(de-space, de-center, tilt)를 측정한 결과 소형위성광학계에 적용 가능한 수준의 정렬도를 갖는 것을 확인하였다.